Strategi Dakwah dalam Pengkaderan Ulama di Dayah Madinatuddiniyah Aswal Hidayatussalam Desa Pasi Jambu Kecamatan Kaway XVI Kabupaten Aceh Barat - Nufus, Zakiaton (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2024)
As time goes by and advances in technology have had an impact on changes in people's lives, such as the destruction of morals. Western culture is used as a reference which unknowingly makes people further away from Islamic teachings. Therefore, it is important to cadre clerics amidst this current of change in order to strengthen moral, ethical and spiritual foundations. This thesis aims to find out how the da'wah strategy of Teungku Dayah Madinatuddiniyah Aswal Hidayatussalam, Pasi Jambu Village, Kaway This research uses descriptive qualitative research methods. Data collection techniques through observation, interviews and documentation. The results of the research show that the da'wah strategy used is the Bi Al Lisan da'wah strategy, namely preaching through verbal/speech and the Bi Al-Hal da'wah strategy, namely the da'wah strategy through actions or empowering students. Meanwhile, the obstacles are the students' low interest in learning, the influence of culture/environment, the decreasing level of students' discipline, low parental motivation, and the economic factors of the students' families. Keywords: Da'wah strategy, Teungku Dayah, Ulama cadre formation